Influence of fin number on hot-carrier injection stress induced degradation in bulk FinFETs. (December 2016) - Zhang, Wenqi; Wang, Tzuo-Li; Huang, Yan-Hua; Cheng, Tsu-Ting; Chen, Shih-Yao; Li, Yi-Ying; Hsu, Chun-Hsiang; Lai, Chih-Jui; Yeh, Wen-Kuan; Yang, Yi-Lin
Abstract: In this paper, hot-carrier injection (HCI) stress has been used to investigate the reliability of n-channel FinFET devices with different fin numbers. Threshold voltage (VTH ) shift, subthreshold swing and transconductance variation were extracted to evaluate the degradation of the device under stress. FinFET devices with fewer fins show more serious performance degradation due to hot-carrier injection stress. It is suggested that the existing of coupling effect between neighboring fins reduces the inversion charge density and equivalent electric field in multi-fin devices, which causes better reliability than single-fin devices. Highlights: Hot-carrier injection (HCI) stress was used to study the reliability of n-channel FinFET devices with different fin numbers. FinFET devices with fewer fins show more serious performance degradation due to hot-carrier injection stress. The existing of coupling effect between neighboring fins reduces the inversion charge density and equivalent electric field in multi-fin devices. Multi-fin devices show better reliability than single-fin devices.